ABAUT THE TRUTH AND MEANING - Oscco López, Rómulo (2014)
The article is to attempt to show the true conception of Wittgenstein presented from the two traditional moments of your posture. In this sense it is necessary to distinguish what determines the direction in language and uses that one presents the use of language. In the same sense tambiéns and makes relevant the question under what conditions a proposition is true and how it is possible to provide a configuration with respect to this proposition, which is why we have to show the difficulties that arise when trying to determine an conception of truth as any meaningful expression contained an image of the world.